Kepemimpinan Profetik Ketua Yayasan dalam Penguatan Budaya Madrasah - Fachri Mohamad Huda; Besse Marhawati; Zulystiawati (Transbahasa, 2026)
This research aims to describe the prophetic leadership of the foundation chairman in strengthening the culture of Al-Huda Islamic School in Gorontalo, including the implementation of prophetic values, internalization strategies, governance reinforcement, and supporting and inhibiting factors. This research uses a qualitative approach with a case study design. Data are collected through interviews, observations, and documentation, and their trustworthiness is established through source and method triangulation and prolonged observation. he results show that the value of siddiq is manifested through integrity, transparency, and consistency in decision-making. The value of amanah is reflected in responsibility, discipline, and direct involvement in carrying out duties. The value of tabligh is evident in courteous, educational, and participatory communication. The value of fathanah is manifested through analytical and adaptive abilities, as well as strategic decision-making in foundation management The reinforcement of foundation governance based on prophetic values is demonstrated through information transparency, direct supervision and mentoring. participatory communication, and competency-based human resource management Habituation strategies are carried out through the internalization of values in daily activities, leadership role modeling, the cultivation of honesty, discipline, open communication, and continuous self-development Supporting factors include the commitment of madrasah members, synergy among stakeholders, a culture of openness, collective concern, and the quality of human resources that balance general knowledge and religious knowledge Meanwhile, inhibiting factors include differences in individual characteristics, low intrinsic motivation, tendencies toward egocentrism in communication, and apathetic attitudes toward the implementation of prophetic values.